Prevalence of Work-Related Musculoskeletal Complaints Among Rehabilitation Professionals: Occupational Therapists, Physiotherapists, and Speech Therapists - Muhammad Luthfi (Jurnal Kesehatan Masyarakat Perkotaan, 2026)
Work-related musculoskeletal disorders (WMSDs) are an occupational health problem frequently experienced by healthcare workers. Rehabilitation professionals such as occupational therapists, physiotherapists, and speech therapists are at risk of experiencing musculoskeletal complaints due to their work involving physical activity, repetitive movements, and non-ergonomic working postures when treating patients. However, data on the prevalence of WMSDs among rehabilitation professionals in Indonesia is still limited. The purpose of this study was to describe the prevalence of work-related musculoskeletal complaints among rehabilitation professionals. Methods: This study used a quantitative observational design with a cross-sectional approach. The study population consisted of 189 rehabilitation professionals at a therapy service provider, with 73 respondents completing an online form. The research instrument used a respondent characteristics form and a Nordic body map (NBM). Results: The prevalence of WMSDs in the last 12 months was 95.9%, while the prevalence in the last 7 days was 83.6%. A total of 61.6% of respondents reported obstacles to daily activities due to musculoskeletal complaints. The most common complaints are in the lower back, shoulders, neck, and upper back. Conclusion: The prevalence of work-related musculoskeletal disorders in rehabilitation professionals is very high. Therefore, preventive measures, improvements in work ergonomics, and occupational health promotion are needed. This study aims to describe the prevalence of work-related musculoskeletal disorders in rehabilitation professionals, including occupational therapists, physiotherapists, and speech therapists.